Analisis Semiotika Transgender dalam Karakter Einar Wegener pada Film Danish Girl (Jurnal Kajian Media, 2017)
The aim of this study is understanding the meaning of transgender within Einar Wegener's character in The Danish Girl. Descriptive Qualitative is used for the technique of data gathering in this study which is with observation and data documentation. The researcher takes scenes those contain transgenderism meaning. In this study, the researcher uses semiotics by John Fiske through 3 levels, which are: reality, representation, and ideology that showing the change before, during, and after. Liberalism is the ideology of the movie. Keywords: Semiotics, The Meaning of Transgender, The Danish Girl